2020
DOI: 10.1021/acsaem.0c00134
|View full text |Cite
|
Sign up to set email alerts
|

LiAlH4 as a “Microlighter” on the Fluorographite Surface Triggering the Dehydrogenation of Mg(BH4)2: Toward More than 7 wt % Hydrogen Release below 70 °C

Abstract: Mg(BH 4 ) 2 is one of the most promising hydrides for hydrogen storage. Herein, the dehydrogenation properties of Mg(BH 4 ) 2 are significantly improved by LiAlH 4 and fluorographite (FGi) addition. The metathesis reaction between Mg(BH 4 ) 2 and LiAlH 4 has been strongly hindered by FGi, and a novel "chocolate cookie" structure is observed that Mg(BH 4 ) 2 and LiAlH 4 particles scatter uniformly on the FGi surface. An unexpected hydrogen desorption capacity of 7.12 wt % is discovered in the Mg(BH 4 ) 2 − LiAl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…58 Compared with the pristine NaBH 4 , NaBH 4 @Na 2 B 12 H 12 displayed two peaks by XPS in the B 1s spectrum shifted to higher binding energies, and this indicates an increase in boron number in NaBH 4 @ Na 2 B 12 H 12 . 59 The same redshift was also observed in the Na 1s narrow scan (Figure 2d), and this may be due to the higher interaction strength between Na + and B 12 H 12 2− in NaBH 4 @ Na 2 B 12 H 12 . 60 The atomic ratio between B and Na is around 7.3 and close to the expected theoretical atomic B/Na ratio of 6 in Na 2 B 12 H 12 .…”
Section: ■ Materials and Methodssupporting
confidence: 67%
“…58 Compared with the pristine NaBH 4 , NaBH 4 @Na 2 B 12 H 12 displayed two peaks by XPS in the B 1s spectrum shifted to higher binding energies, and this indicates an increase in boron number in NaBH 4 @ Na 2 B 12 H 12 . 59 The same redshift was also observed in the Na 1s narrow scan (Figure 2d), and this may be due to the higher interaction strength between Na + and B 12 H 12 2− in NaBH 4 @ Na 2 B 12 H 12 . 60 The atomic ratio between B and Na is around 7.3 and close to the expected theoretical atomic B/Na ratio of 6 in Na 2 B 12 H 12 .…”
Section: ■ Materials and Methodssupporting
confidence: 67%
“…Such behavior was due to the oxygen atoms present as functional groups that improve the decomposition of the intermediates of LiBH 4 . Similarly, Zheng et al reported the dehydrogenation behavior of Mg­(BH 4 ) 2 with the addition of LiAlH 4 and fluorographite (FGi). The authors proposed formation of a unique morphology by the reaction between Mg­(BH 4 ) 2 and LiAlH 4 , which led to the uniform distribution of Mg­(BH 4 ) 2 and LiAlH 4 particles on the surface of FGi.…”
Section: Introductionmentioning
confidence: 91%
“…The reason for this low dehydrogenation temperature was explained by the lower activation energy of the dissociation of the B-H bond, which was supported by density functional theory calculations. Further improvements were achieved through synergic effects by combining different strategies, including catalyzed composites [197,[230][231][232], by incorporating catalysts directly onto the scaffold [233][234][235], by nanoconfining composites [236,237] or by synthesizing nanoparticles (NPs) on fluorographites (FGi) [201,238]. As an example of the latter strategy, homogeneous dispersed NPs of Mg(BH 4 ) 2 and LiAlH 4 were achieved on an FGi substrate to form a "chocolate cookie" structure.…”
Section: Nanoconfinementmentioning
confidence: 99%